Fortifikasi Minyak Ikan Jambal Siam (Pangasius hypophthalmus) dan Minyak Ikan Kerapu (Chromileptes sp) Pada Biskuit - Anisa Ramadhani; Mirna Ilza; Desmelati Desmelati (Berkala Perikanan Terubuk, 2015)
The study was conducted to determine the level of consumer acceptance and chemical composition of biscuit added with cat fish oil and gruoper oil. About 1 kg of abdominal fat from cat fish and 1 kg of gruoper meat was taken from a fish market in Pekanbaru was prepared,then fish oil could be proccessed. Three types of biscuit were fortifed with 0%, 10% and 20% of cat fish oil and grouper oil. Biscuit was evaluated for consumer acceptance and chemical composition (water, lipid, protein and free lipid acids). The results indicated that biscuit was fortified with 10% of cat fish oil and gruoper oil was the most prefereble by consumer. Water, lipid, protein and free lipid acids content of biscuit was 3,01%, 10,04%, 5,57% and 0,15% respectively.